Allelopathic effects of aqueous extract of liquorice (Glycyrrhiza glabra L.) on seed germination and seedling growth of wheat and some weed species - Mustafa, Kawa Faisal; Khasraw1, Muhammed Najeeb; Tahir, Nawroz Abdul-razzak; Nadir, Shangeen Hama Salih; Mahmood, Hikmat Noori (Sulaimani Journal for Pure and Applied Sciences, 2018)
A laboratory experiment using completely randomized design with three replicates was conducted in April 2015, to evaluate the germination and seedling growth of three plant types; Wheat (Triticum aestivum L.), Wild oat (Avena fauta L.) and Milk thistle (Silybum marianum L.) seeds were soaked in distilled water (control), 30 and 50% of liquorice (Glycyrrhiza glabra L.) leaf and root aqueous extracts to study the allelopathic potential effects of them. Whereas liquorice leaf and root aqueous extracts concentrations increased from 30 to 50%, the inhibitory effect of allelopathic materials on germination, growth, and seed vigour index, fresh and dry weight of seedling also increased. The results showed that S. marianum was the most sensitive to liquorice leaf and root extracts than A. fauta., although both were most sensitive to leaf and root extract. Wheat seeds were the most resistant to liquorice leaf and root extracts than both weed seeds. Leaf and root aqueous extracts showed non-significant different between them for all studied traits. The strong negative relationship was observed among extract concentrations and studied parameters.
Keywords: Allelopathy; Liquorice; germination; weed aqueous extract and wheat